Effect of Tapioca Binder Concentration on the Quality of Charcoal Briquettes Produced from Oil Palm Trunk and Laban Wood - Hisyammudin Hisyammudin; Zakwan Zakwan; Heri Purwanto (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This study examined the effect of tapioca binder concentration on the quality of charcoal briquettes produced from oil palm trunk and laban wood. A non-factorial Completely Randomized Design was applied using five binder concentrations: V1 (10%), V2 (15%), V3 (20%), V4 (22.5%), and V5 (25%), with three replications. Moisture content, ash content, and calorific value were evaluated. One-way analysis of variance showed a highly significant treatment effect for every parameter (p < 0.001), and Duncan’s Multiple Range Test at the 5% level separated all treatment means. Increasing binder concentration raised moisture content from 4.131% to 6.175% and ash content from 3.263% to 4.900%, while calorific value decreased from 7,185.33 to 6,325.98 cal/g. All treatments met SNI 01-6235-2000. The best treatment was V1, consisting of 47.5% oil palm trunk charcoal, 47.5% laban wood charcoal, and 10% tapioca binder. The results demonstrate that controlling binder concentration is essential for balancing particle cohesion and thermal quality.